MODEL INTEGRASI 2 STAGE DATA ENVELOPMENT ANALYSIS-MONTE CARLO UNTUK PEMILIHAN PARTNER SUBKONTRAK - Putri, Maulin Masyito (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2017)
With cheaper consideration, product subcontracting often becomes an option. So far the selection of subcontractors is based solely on the price of the cheapest contract offered. Apparently not enough, there are still some input and output variables that must be considered. So far, the existing methods still have some weaknesses. The classic DEA model often fails to work effectively because it is very sensitive to statistical changes. Meanwhile the AHP and DEMATEL methods are not appropriate when the unequal monthly risk frequency is encountered. So we need to develop new method, that is integration 2 Stage Data Envelopment Analysis (DEA) -Monte Carlo. Using VBA-excel based simulation assistance, it can be concluded that the most appropriate subcontract partner for UV process is DMU 1A (Central Coating) while subcontract partner for embossed process is DMU 1B (Super Indah Langgeng) and the most appropriate subcontracted laminating process partner is DMU 1C is (Central Coating), each having the best productivity with low risk level. Key Word: Subcontract Selection, Eficiency, Productivity, 2 Stage DEA-Monte Carlo